The Meaning of Retirement: Cross-national Patterns and Trends - Timothy Smeeding (Luxembourg Income Study (LIS), 1990)
LIS database is used to demonstrate the complexity of defining 'retirement,' examine the patterns of several definitions of retirement across nations, investigate the impact of retirements on poverty, and look at the variations in retirement across time.
Keywords: 330